Analisis Perubahan Makna Dalam Ilmu Semantik - Zamharil (An Nazhair: Journal of Arabic Education, 2024)
This paper aims to explore how meaning changes occur in semantic science, especially in Arabic. semantics has long been a subject of interest to language and literature researchers. Basically, semantics studies meaning in language, including how the meaning of words and sentences can change over time. This research uses a descriptive qualitative approach with a literature study method. The results in this study reveal that the change in meaning is a shift from the first meaning to the next meaning in which the change in meaning is influenced by various factors so as to bring up a new meaning according to the needs of the speaker. There are at least five factors that cause changes in meaning in a language including; Socio-cultural developments, sensory exchange responses, differences in the field of use, developments in the field of science and technology, language absorption factors from different generations. The forms of meaning change, namely, expansion of meaning, narrowing of meaning, amelioration and peyoration